2020
DOI: 10.3390/cells9071724
|View full text |Cite
|
Sign up to set email alerts
|

The Secretome Analysis of Activated Human Renal Fibroblasts Revealed Beneficial Effect of the Modulation of the Secreted Peptidyl-Prolyl Cis-Trans Isomerase A in Kidney Fibrosis

Abstract: The secretome is an important mediator in the permanent process of reciprocity between cells and their environment. Components of secretome are involved in a large number of physiological mechanisms including differentiation, migration, and extracellular matrix modulation. Alteration in secretome composition may therefore trigger cell transformation, inflammation, and diseases. In the kidney, aberrant protein secretion plays a central role in cell activation and transition and in promoting renal fibrosis onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Renal fibroblasts quiescently reside in renal interstitium and play an essential role in ECM homeostasis for maintaining the kidney ultrastructure and function 61 , 62 . During fibrogenesis, the quiescent fibroblasts are activated and display a spindle-shaped, mesenchymal phenotype, known as myofibroblasts 63 , 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Renal fibroblasts quiescently reside in renal interstitium and play an essential role in ECM homeostasis for maintaining the kidney ultrastructure and function 61 , 62 . During fibrogenesis, the quiescent fibroblasts are activated and display a spindle-shaped, mesenchymal phenotype, known as myofibroblasts 63 , 64 .…”
Section: Discussionmentioning
confidence: 99%
“… 96 Excessive production of this cytokine over time drives the accumulation of myofibroblasts, cells that deposit large amounts of ECM proteins, including collagens (Figure 3 ). 97 , 98 The exact precursor cell that gives rise to myofibroblasts is not well understood, although it has been proposed that they may arise from epithelial to mesenchymal transition, endothelial to mesenchymal transition, fibrocyte recruitment, pericyte recruitment, and resident fibroblast recruitment. 99 TGF- β pathway activation also results in activation of the NLRP3, Smad3, and Caspase-1 stimulators, which further exacerbate renal fibrosis.…”
Section: M2 Macrophage (Proreparative) Pathwaysmentioning
confidence: 99%
“…Myofibroblasts will continue to produce more ECM components. Consequently, the imbalance of ECM synthesis and degradation promotes the deposition of ECM components in the kidney, thereby induing glomerular sclerosis and renal fibrosis ( 42 ). Studies have confirmed that renal fibrosis is the common pathological process during the progression of AKI to CKD ( 43 ).…”
Section: Macrophages In Kidney Injury Repair Regeneration and Fibrosismentioning
confidence: 99%